A Generating Balanced Scorecard as Performance Measurement Framework for Secondary Education: A Case Study at Singapore National Academy - srikanthi, yulia ayu (Universitas Ciputra Surabaya, 2024)
Learning from recent phenomena in education field, schools must adopt strategic management practices to survive in turbulent environment. Secondary education, in particular must have strategic goal and must be able to measure the performance of key areas to achieve that goal. This study’s main objective is generating a Balanced Scorecard (BSC) as a performance measurement framework for Secondary education, using Singapore National Academy as the case study. The study aims to describe how the school can move from mission to vision using goals and objectives articulated in its strategic plan 2023-2027 with its focus goal of 200% of student growth. The study uses a qualitative research approach. It comprises an extensive review of relevant literature, an in-depth analysis of the school’s strategic plan, and a comprehensive discussion and face-to-face interview with total of 10 key sources. Benchmarking with similar school (Sekolah Citra Kasih / Sekolah Citra Berkat) was also used to generate the BSC framework. The result shows that there are 12 strategic objectives to achieve the focus goal which have been grouped into four BSC perspectives: Financial, Customer, Internal Business Process and Learning & Growth. These strategic objectives then were broken down into 25 measurement indicators with each one is equipped with a